2022
DOI: 10.1002/jmv.27849
|View full text |Cite
|
Sign up to set email alerts
|

Individual genetic variability mainly of Proinflammatory cytokines, cytokine receptors, and toll‐like receptors dictates pathophysiology of COVID‐19 disease

Abstract: Innate and acquired immunity responses are crucial for viral infection elimination. However, genetic variations in coding genes may exacerbate the inflammation or initiate devastating cytokine storms which poses severe respiratory conditions in coronavirus disease-19 (COVID-19). Host genetic variations in particular those related to the immune responses determine the patients' susceptibility and COVID-19 severity and pathophysiology. Gene polymorphisms such as single nucleotide polymorphisms (SNPs) of interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 109 publications
0
15
0
1
Order By: Relevance
“…Inflammatory responses to viral infection are also influenced by genetic background, for example individual genetic variability of pro-inflammatory cytokines is related to severity in COVID-19 ( Vakil et al., 2022 ). Moreover, population-associated variation of responses to viral infections is differentiated by genetic ancestry ( Randolph et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory responses to viral infection are also influenced by genetic background, for example individual genetic variability of pro-inflammatory cytokines is related to severity in COVID-19 ( Vakil et al., 2022 ). Moreover, population-associated variation of responses to viral infections is differentiated by genetic ancestry ( Randolph et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of rs13306435 in HCC has been confirmed by meta-analysis (HCC) [1], [7], [21]. SNPs rs13306435 (-395T > A), rs2069860 (-623A > T), and rs2069830 (-612A > T) were shown to have a substantial correlation with cervical cancer susceptibility in the Lithuanian population in a separate research that evaluated two IL-6 genetic polymorphisms (rs13306435 and rs2069830) [6], [15], [16].…”
Section: Discussionmentioning
confidence: 98%
“…There was a correlation between the 395 A/T rs2069830) SNP and COPD in Caucasians but not in North Indians. One research found an association between the IL-6 rs2069830 (-612A > T) CC gene variant and the risk of dying from septic shock in Caucasian Europeans who had heart or abdominal surgery [16], [17]. Researchers from China discovered that those with the IL-6-395 TT genotype had a significantly increased likelihood of developing pneumonia-induced sepsis and mRNA levels [18]- [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also indicated a high infectivity potential and increased severity of COVID-19 in the A blood group serotype, while the O blood group serotype is observed to be protective against infection [18]. Genetic polymorphism, SNPs, in-host immune response genes, including interferons, TNF, and interleukins, are attributed to inducing a high COVID-19 severity [19]. Additionally, besides the genetic and immune determinants, age and gender association has been widely observed in COVID-19 infectivity and severity [20,21].…”
Section: Introductionmentioning
confidence: 99%